PENGARUH PERUBAHAN HARGA BAHAN BAKAR MINYAK (BBM) TERHADAP TINGKAT INFLASI DI INDONESIA - Harunurrasyid Harunurrasyid (Jurnal Ekonomi Pembangunan, 2013)
This research aims at analyzing the effect of the change of oil price (BBM) on inflation rate in Indonesia. The main data used were the change of oil price and inflation rate  taking  period of 34 years ranging from April 1979 to June 2013. The result of  regression analysis shows that the effect of the change of oil price (BBM) on the inflation rate in Indonesia is positive. It can be concluded that an increase of the oil price by 1 % will lead to an increase of infaltion rate by 0,51%. The effect of the oil price is more dominant on the rate of inflation  which is grouped in expenditures for raw materials of food, tranportation dan communication than on inflation rate of other group of expenditures. Keyword: The Change of Oil Price (BBM) and Inflation Rate.